A simple low-cost tool to predict the risk for oesophageal carcinoma: a validation study - Ishanka Ayeshwari Talagala; Metthananda Nawarathne; Carukshi Arambepola (College of Community Physicians of Sri Lanka, 2022)
Introduction: Oesophageal carcinoma (OC) is a leading cancer in Sri Lanka. Owing to late symptoms and absence of routine endoscopic screening, delayed presentation leads to severe outcomes of the patients with OC.   Objectives: To develop and validate a simple low-cost risk prediction tool to identify high-risk individuals for OC early, based on population-specific risk   Methods: A risk prediction tool including cut-off value to identify high-risk individuals, was developed based on weighted scores derived from the risk factor profile specific for Sri Lankans. Its criterion validity was assessed against histological diagnosis of OC in an unmatched case-control study conducted among 83 cases recruited from the National Cancer Institute, Maharagama (NCIM) using a non-probability sampling method, and ambulatory hospital controls (n= 166) excluded of OC recruited from the Endoscopy Unit at National Hospital of Sri Lanka (NHSL ). Data were collected through an interviewer-administered-questionnaire.   Results: Risk predictors in the tool included age >65 years, family history of cancer, sub-optimal consumption offibre, antioxidants and deep-fried food, low total lifetime sports and exercise activities, high risk alcohol consumption, ever betel quid chewing, ever exposure to agrochemicals, consumption of pipe-borne water, ever exposure to radiation and ever tobacco smoking. The tool demonstrated valid predictions (92.8% sensitivity; 88.6% specificity; 80.2% positive predictive value (PPV); 96.1 % negative predictive value (NPV); 8.1 positive likelihood ratio (LR); and 0.1 negative LR) to identify high-risk individuals for OC at 17 .83 cut-off value.   Conclusions & Recommendations: To minimize delayed diagnosis and improve survival, this simple and low-cost risk prediction tool is recommended for identifying and prioritizing high-risk individuals for endoscopy screening for OC.